Association of biomarkers and Barthel Index with occurrence of age‐related adverse health outcomes in individuals with diabetes - Kotaro Umamoto; Ryotaro Bouchi; Kotaro Soeda; Shosuke Satake; Tohru Hosoyama; Mitsuru Ohsugi; Kohjiro Ueki; Hiroshi Kajio (Journal of Diabetes Investigation, 2024)
Abstract Aims/Introduction The clinical significance of age‐related biomarkers in patients with diabetes has not been fully elucidated. In this study, we aimed to establish models to predict the progression of aging in patients with diabetes using biomarkers. Materials and Methods This single‐center, retrospective cohort study included 115 Japanese patients with diabetes aged ≥60 years. Age‐related adverse health outcomes were defined as emergency hospitalization, any increase in the level of nursing care certification, admission to a nursing home or death. The associations of age‐related biomarker levels (adiponectin, growth differentiation factor 15 [GDF15], C‐X‐C motif chemokine ligand 9 and apelin) and clinical indicators with age‐related adverse health outcomes were evaluated. Factors that predominantly influenced the occurrence of age‐related adverse health outcomes were explored using the Cox proportional hazards model. Results The mean age of the 115 participants was 73 years, 50.6% were men, the mean body mass index and hemoglobin A1c level were 25.3 kg/m2 and 9.79%, respectively. There were 26 age‐related adverse health outcomes during the study period (median 1.93, range 0–4.65 years). In a model combining clinical indicators and biomarkers, including the Barthel Index, GDF15 and adiponectin, the occurrence of age‐related adverse health outcomes was found to be significantly associated with GDF15 and Barthel Index. The group with both GDF15 and adiponectin levels higher than the median proved to be significantly higher than the group with both lower. Conclusions The measurement of GDF15 and adiponectin levels and the Barthel Index might be useful for predicting age‐related adverse health outcomes in patients with diabetes.